Horizontal mattress technique for anastomosis of size-mismatched vessels. Issue 2 (May 2015) - Odobescu, Andrei; Moubayed, Sami P; Daniels, Eugene; Danino, Michel Alain
Objective: To evaluate the horizontal mattress technique in microvascular anastomosis for size-mismatched vessels. Methods: The present study involved cadaveric simulation using size-mismatched (1.5:1) Thiel-embalmed cadaveric arteries. The authors performed horizontal mattress anastomoses using 9-0 nylon suture and recorded the procedure. Vessel patency was evaluated by saline infusion. Vessels were cut open and photographed; histological slides were prepared and stained with hematoxylin and eosin. Results: Four anastomoses were performed. Vessels were found to be patent in all cases, with grade 0 leaks. Intima-on-intima apposition with no intraluminal exposure of muscularis nor adventitia were observed. Conclusion: The present cadaveric study supports the technical feasibility of using horizontal mattress sutures in size-mismatched end-to-end anastomoses.